Overall Decrease in the Susceptibility of Mycoplasma bovis to Antimicrobials over the Past 30 Years in France - Gautier-Bouchardon, Anne V. (Public Library of Science, 2014)
Mycoplasma (M.) bovis is frequently implicated in respiratory diseases of young cattle worldwide. Today, to combat M. bovis in Europe, only antimicrobial therapy is available, but often fails, leading to important economical losses. The antimicrobial susceptibility of M. bovis is not covered by antimicrobial resistance surveillance networks. The objectives of this study were to identify resistances that were acquired over the last 30 years in France and to determine their prevalence within comtemporary strains. The minimum inhibition concentration (MIC) values of 12 antimicrobials, considered active on M. bovis, were compared, using an agar dilution method, between 27 and 46 M. bovis isolates respectively obtained in 1978–1979 and in 2010–2012 from 73 distinct respiratory disease outbreaks in young cattle all over France. For eight antimicrobials, resistances were proven to be acquired over the period and expressed by all contemporary strains. The increase of the MIC value that inhibited 50% of the isolates (MIC(50)) was: i) substantial for tylosin, tilmicosin, tulathromycin and spectinomycin, from 2 to >64, 2 to >128, 16 to 128 and 4 to >64 µg/mL, respectively, ii) moderate for enrofloxacin, danofloxacin, marbofloxacin and oxytetracycline, from 0.25 to 0.5, 0.25 to 0.5, 0.5 to 1, 32 to >32 µg/mL, respectively. No differences were observed for gamithromycin, tildipirosin, florfenicol and valnemulin with MIC(50) of 128, 128, 8, <0.03 µg/mL, respectively. If referring to breakpoint MIC values published for respiratory bovine pathogens, all contemporary isolates would be intermediate in vivo for fluoroquinolones and resistant to macrolides, oxytetracycline, spectinomycin and florfenicol.